Does Despotic Leadership Harm Employee Family Life: Exploring the Effects of Emotional Exhaustion and Anxiety - Nauman, Shazia; Fatima, Tasneem; Haq, Inam Ul (Frontiers in Psychology, 2018)
Research has not focused on the negative effects of despotic leadership on subordinates ‘life satisfaction and the interface between work and family. Drawing on the Conservation of Resources theory, this research investigates the mediating effect of emotional exhaustion through which despotic leadership transcends from the workplace to subordinates’ personal lives, resulting in work-family conflict and decreased life satisfaction. The research also examines the moderating effect of subordinates’ anxiety on the relationship of their perceptions of despotic leadership with work-family conflict and life satisfaction. Three waves of time-lagged data was collected from 224 book sellers who work in publishing houses. We used Hayes’ PROCESS to test moderation and SEM to test mediation. The results of the study suggest that despotic leadership is related to work-family conflict via emotional exhaustion, but offer no support for its relationship with life satisfaction. As expected, when subordinates’ anxiety increases, the positive relationship between a supervisor’s despotism and his or her subordinates’ work-family conflict and the negative relationship between despotic leadership and life satisfaction both strengthen. The results suggest that despotic leaders harm their subordinates’ non-work lives, and these effects intensify when subordinates have high levels of anxiety. These findings have important implications for service organizations in mitigating the negative effects of despotic leadership by minimizing subordinates’ anxiety through coping mechanisms and giving rewards and incentives to salespersons.